ANALYSIS OF RESPONSIBILITY FACTORS IN THE IMPLEMENTATION OF SOCIAL ASSISTANCE PROGRAMS IN THE SOCIAL SERVICES OF GUNUNGSITOLI CITY - Yulexna Mendrofa; Eliagus Telaumbanua; Syah Abadi Mendrofa; Sophia Molinda Kakisina (Jurnal Ilmiah METADATA, 2026)
This study aims to analyze employee responsiveness in the implementation of the National Health Insurance Contribution Assistance Recipient (PBI JKN) program during the Integrated Social Welfare Data (DTKS) verification process at the Gunungsitoli City Social Service. The research focuses on factors influencing employee responsiveness and efforts made to overcome technical service constraints. The study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. Research informants consisted of leaders and employees directly involved in the issuance of PBI JKN reactivation certificates. The research results indicate that employee responsiveness in providing JKN PBI services is not yet optimal, primarily due to limited human resource quality, unstable internet networks, limited facilities and infrastructure, and the complexity of the bureaucratic structure. On the other hand, internal communication, leadership, and employee commitment are supporting factors in accelerating the service process. Efforts to address technical challenges include coordination between employees, maximizing the use of information technology, and providing assistance to the community during the DTKS verification process. This study concludes that increasing employee responsiveness requires strengthening human resource capacity, improving technological infrastructure, and simplifying bureaucratic procedures. These findings are expected to provide evaluation material for local governments in improving the quality of public services, particularly in the implementation of social assistance programs.